Climate change: attribution of extreme weather - Otto, F (Nature, 2015)
Anthropogenic climate change alters the risk of some extreme weather events. High-resolution computer simulations suggest that Black Sea warming made the devastating 2012 Krymsk flood possible — a virtually impossible event just 30 years ago.